Handbook of trade control measures of developing countries 1987 (UN New YorkUS, 1987)
Outlines measures put in place by developing countries to regulate their trade flows. These are summarized under ten headings viz. tariff charges, additional fiscal charges, service charges with equivalent effect, internal taxes levied on imported and domestic products, licensing and quantitative restrictions, money and finance measures, control of price level, single channel for imports and compulsory national services, preferential trading arrangements, and special entry procedures. Lists state trading organizations within most of the countries mentioned.
IDS